NAFTA 이후 멕시코 농업의 변화 분석 - 김윤식 (한국농촌경제연구원, 2006)
This research is designed to investigate what happened to the Mexican agriculture after NAFTA (North America Free Trade Agreement). The purpose of the Mexican case study is to find what implications Korea could obtain from Mexico because Korea is negotiating an FTA with the United States. NAFTA was in effect in 1994. Mexico is important in that Mexico is the first developing country signed an FTA with the United States. In addition, 12 years have passed since Mexico had joined NAFTA. 12 years are enough time that a lot of data needed to analyze the effect of NAFTA are accumulated. It is certain that Mexican agricultural GDP grew and export increased after NAFTA. However, the overall evaluation of the impact of NAFTA on the Mexican agriculture is controversial because the GDP growth gap among states was widened and the import increased faster than export. Of course, it is not easy to judge whether NAFTA has overall a positive impact on the Mexican agriculture or not. Some sectors benefited from NAFTA while other sectors lost from NAFTA. The sectors benefited would evaluate the effect of NAFTA positively but the sector lost would not. To mitigate the impact of NAFTA on agriculture, new policies were introduced. CONASUPO (the Compania Nacional de Subsistencias Populares), intervened with agricultural market through purchases and resales, was phased out in the market and abolished in 1999. CONASUPO protected producers by purchasing grains at higher price and supported consumers by reselling the commodities at lower price. CONASUPO was replaced with ASERCA (Apoyos y Servicios a la Comercializacion Agropecuaria), which was established in 1993. Under ASERCA, producers were paid the difference between policy price and international price. In addition, the payment was given only producers who belonged to some specific states where there existed production surplus. Later, this was extended to producers who had production surplus. The supports for consumers were almost abolished. A direct payment scheme, PROCAMPO (Programa de Apoyos Directos al Campo), was also introduced. The land owners who planted some grains for 3 years before 1993 were eligible for the payment. The producers who own less than 1 ha were paid the same rate as the producers who own 1 ha. Furthermore, the growers whose land are between 1 ha and 5 ha were paid higher rate than other growers. In 2003/04, 935 peso/ha were paid while 1,120 peso/ha were paid for size of 1-5 ha farms. The trend of per capita GDP was analyzed. NAFTA contributed to the increase in per capita GDP. However, the difference with per capita GDP of the U.S. was widened. That means that an FTA is not sufficient for developing countries to catch up with developed countries. After NAFTA, exports to the U.S. increased but imports to Mexico increased more. Thus, trade balance in agriculture was not improved. The corn market was also investigated. Corn in Mexico is the same as rice in Korea. There are two types of corn in Mexico: white corn and yellow corn. White corn, produced in Mexico, is usually used for food while yellow corn, imported from the U.S., is used for animal feed. Since NAFTA, corn production in Mexico continued to increase despite downward trend of corn price and substantial increase in imported corn. The plausible explanation is as follows; the substitutability between white and yellow corn is very low, so these two market are actually separated; government supports for producers of the Southern Mexico keep them producing traditional grains irrespective of market situation. It is not certain that such effects are caused by NAFTA because it was not affected by abolishment of tariff but the direct payment. It is likely to be indirect impact because the direct payment was introduced to mitigate the direct impact of NAFTA. The lower price of imported corn also has positive impacts on pork and poultry producers by decreasing production cost. After NAFTA, production of pork and chicken increased rapidly due to strong demand and lower production cost. The Northern states benefited from NAFTA through trade with the U.S. The production of vegetables and fruits shows a rapid increase in these states. However, the Southern states hardly benefited from NAFTA. Thus, the gap in per capita income between the Northern and the Southern states tends to have been large over time. Researchers: Yun-shik Kim, Yoonjae Hwang, Songsoo Lim E-mail address: yunshik@krei.re.kr